Analisis morfometri rajungan (Portunus sanguinolentus) di PPI Ujong Baroh, Kabupaten Aceh Barat - Agusriati Muliyana; Rika Astuti; Mila Sulasti; Hayatun Nufus (Universitas Teuku Umar, 2025)
Three-spotted swimming crab (Portunus sanguinolentus), a member of the class Malacostraca within the Crustacea, is widely distributed in marine waters. The swimming crab fishery in Aceh possesses high economic value. However, increasing fishing pressure by local fishers has resulted in declining population stocks. This study was conducted to examine the morphometric variation and growth patterns of P. sanguinolentus. The research was carried out at Ujong Baroh Fishing Port (PPI), West Aceh Regency, employing both quantitative and qualitative methods. Sampling was performed using a Simple Random Sampling approach. A total of 104 specimens were collected. Morphometric analysis revealed that the growth parameter b was <3, with a value of 2.4099, indicating a negative allometric growth pattern, in which carapace width increases at a faster rate than body weight. The regression equation describing the relationship between carapace width and body weight was W=0.0006CW2.4099, with a coefficient of determination (R2) of 0.756 and a correlation coefficient (r) of 0.869. The correlation coefficient suggests a strong relationship between carapace width and body weight, as the r value exceedes 0.7. This indicates that increases in carapace width exert a significant influence on body weight growth. The mean carapace width of the male and female groups was 90.0 mm, while the smallest morphometric character recorded was the interorbital distance (8.2 mm), with a standard deviation of 18.4 mm. The mean condition factor of the crabs in West Aceh waters was 1.033, signifying that the overall condition of P. sanguinolentus in the study area is considered healthy.